FEATURES OF THE ALVEOLAR BONE MUCOUS MEMBRANE CELLULAR COMPOSITION RESTRUCTURING IN CASE OF PREMATURE LOSS OF TEETH - Gevkaliuk, N.О.; Machogan, V.R. (World of Medicine and Biology, 2019)
The fundamental work of orthopedic dentistry is devoted to solving the problems of increasing the functional effectiveness of prostheses in patients with partial and complete loss of teeth, however, in case of adverse anatomical and physiological conditions prosthetics of toothless jaws with laminar removable dentures is not always effective and requires prediction. The article provides a detailed description of the study of the cellular composition of smears-scrapings of cytograms of the alveolar processes of patients with premature loss of teeth, makes it possible to predict atrophic processes and complications associated with correction.
Keywords: cell; atrophy; prosthetics; gum; partial adentia